THU0394 Macrophage activation syndrome in adult onset still's disease: A single center experience. (23rd January 2014) - Damian, L.O.; Felea, I.; Simon, S.-P.; Lupse, M.; Bodolea, C.; Ghib, L.; Mocanu, R.; Rednic, S.
Abstract : Background: Macrophage activation syndrome (MAS) is an increasingly recognised life-threatening complication of autoimmune diseases, occurring mainly in systemic-onset juvenile idiopathic arthritis (SoJIA) and adult-onset Still's disease (AOSD). Objectives: The aim of this study is to describe the clinical features and therapy of MAS in AOSD from a single Romanian medical center. Methods: The medical charts of AOSD patients seen between 2001 and 2011 in a tertiary referral center were reviewed in order to identify the cases of MAS. The adult patients with MAS and SoJIA were excluded. All patients with AOSD met the Yamaguchi criteria. MAS was diagnosed using the preliminary Ravelli criteria for SoJIA. Clinical and laboratory assessments were recorded comparatively for a patient in the episode of MAS and outside of it. Results: Between the 61 patients with AOSD identified, 6 patients (4 M, 2 F, aged 24-72 years, mean age 47 yrs) had at least one flare of MAS. In 2 patients MAS was the inaugural feature of AOSD. During the MAS episode all patients hadhigh- grade continuous fever, CNS involvement and hepatomegalia. Interstitial lung involvement was seen in 4 cases. Arthritis was not prominent during the episode. Five patients had thrombocytopenia, 3 had leukopenia and all had moderate to severe anemia. Hemophagocytosis was histologically confirmed in only two cases. Ferritin values were high (460 to 22000) in all 5 cases in whom it was available; however the degree of elevation was not a reliable marker for MAS. Elevated liver enzymes and hypertriglyceridemia were constant features; hyposodemia was present only in 2 patients. Despite the coagulation abnormalities found in 4 cases, only one patient had hemorrhages. Of interest, the 4 patients with hypocomplementemia (C3 and/or C4) had a more severe form of disease and lung involvement. The therapy consisted in pulsed methylprednisolone (6 pts), mechanical ventilation (1 pt), plasmaferesis (1 pt), cyclosporine (4 pts), azathioprine (2 pts), methotrexate (1 pt), hydroxychloroquine (1 pt), colchicine (1 pt) and oral corticosteroids, according to clinical picture. After recovery from MAS, the blood cell counts and complement titers returned to normal or high values. Conclusions: A high index of suspicion is necessary to identify the patients at risk for MAS in AOSD. Low blood cell counts, hypocomplementemia, hypertriglyceridemia and coagulation abnormalities could help to discriminate between a flare of AOSD and MAS, but validated guidelines are needed. Disclosure of Interest: None Declared